TikTok’s Impact on Generation Z’s Mental Health and Social Relationships - Tri Yunita Nabila; Ismail Ismail (Journal of General Education and Humanities, 2025)
This study aims to understand the impact of TikTok social media use on the mental health of Generation Z in social relationships. As one of the most popular digital platforms among today's youth, TikTok significantly shapes its users' mindset, emotions, and social behaviour. This study used a qualitative approach with descriptive methods, through in-depth interviews and observations of several residents aged 17-22 years old around the Griya Martubung area who actively use TikTok. The findings indicate that TikTok has both positive and negative impacts on the mental health of Generation Z. Positive impacts include increased self-confidence, self-expression, and access to information. However, negative impacts include social anxiety, feelings of inadequacy, and dependence on social views in the form of likes and comments. Several respondents experienced decreased direct interactions in social relationships due to a greater focus on online interactions. This study emphasises the importance of digital literacy and the role of mentors from the surrounding environment to prevent TikTok use from negatively impacting the mental health and quality of Generation Z's social relationships.